The global NPP dependence on ENSO: La Niña and the extraordinary year of 2011. Issue 3 (11th September 2013) - Bastos, A.; Running, Steven W.; Gouveia, Célia; Trigo, Ricardo M.
Abstract : [1] Global ecosystems remove about 25% of anthropogenic CO2 emissions; however, the response of the land sink to climate variability and change is not yet fully understood. In 2011, the highest global value of net primary production (NPP) since 2000 was registered on the Moderate Resolution Imaging Spectroradiometer record, together with the highest value on the Carbon Dioxide Information Analysis Center record of carbon land sink strength since 1959. Here we show that El Niño/Southern Oscillation (ENSO) is responsible for much of the variability observed in the land sink and that the high NPP anomaly observed in 2011 was largely influenced by the strongest La Niña since the 1970s that lasted from late 2010 to early 2012. ENSO explains more than 40% of global NPP variability, mainly driven by the response of Southern Hemisphere ecosystems, particularly in tropical and subtropical regions. Water availability, controlled by temperature and precipitation anomalies, appears to be the main factor driving the regional response of NPP to ENSO. Key Points: Global NPP is strongly anti‐correlated to El-Nino Southern Oscillation Water availability in southern sub‐tropical ecosystems drives this relationship The remarkable La‐Nina in 2011 enhanced the carbon uptake by land ecosystems